Het beroep op de Emder synode in de Afscheiding - Klinken, G. J. van (Kerk en theologie, 2022)
The ideal of the Emden Synod of 1571 was to ensure a degree of autonomy for local Reformed churches. Three hundred years later, Emden was still remembered by the Secessionist churches in the Netherland. They affirmed the principle that those who did not belong to the traditional elite in church and society, still could actively take part in church leadership. This "bottom up"-principle maintains its relevance for "churches of the poor", anywhere in the world.